Hadis tentang Menjaga Diri dari Bahaya Virus di Masa Pandemi Covid-19: Studi Takhrij dan Syarah Hadis - Saiful Muttaqin; Muhamad Yoga Firdaus; Carsam (Gunung Djati Conference Series, 2022)
The purpose of this study is to discuss the hadith about protecting oneself from the dangers of the virus during the Covid-19 pandemic. This research is included in the type of qualitative research with a literature review through the takhrij and syarah hadith methods as well as contemporary analysis. The results of this study are based on the takhrij hadith process about protecting yourself from the dangers of the virus during the Covid-19 pandemic, which is a valid hadith. The syarah of hadith from this hadith research describes how a person must protect his life by protecting himself from the dangers that threaten him, explanation by giving reasons why humans were created, then Allah's love for his creatures, and protecting himself from a situation that endangers his life is one form of his piety to Allah swt. The conclusion of this study is that the hadith about protecting oneself from the dangers of the virus during the covid-19 pandemic is a valid hadith and is the basis for why a person should prevent himself from entering a country where there is a virus or epidemic. This research has many shortcomings and recommends a re-examination through the approach of the science of hadith itself and a sciences that discusses the reasons why a person must protect his life or protect himself from dangerous situations.